Persepsi Masyarakat Kota Pontianak Terhadap Wacana Redenominasi Rupiah Di Indonesia (Studi Kasus Pelaku UMKM Di Kota Pontianak) - Ekajaya, Candra; Syahbudi, Syahbudi; Bustami, Bustami; Safri, Hayanuddin (CV. ITTC INDONESIA, 2024)
Redenomination is included in the Ministry of Finance's 2020-2024 strategic plan and will be realized in the near future. Redenomination offers many benefits for the economy, but its implementation must be careful to avoid hyperinflation. One important factor in the success of redenomination depends on people's knowledge about redenomination, which will influence their perceptions. Wrong perceptions can make people reject redenomination because it is considered the same as sanering. Therefore, a study of public perception is needed before implementing redenomination. This research uses the Spearman Rank Correlation method with a sample of 100 MSMEs in Pontianak City. Data was collected through a questionnaire with a 5 point Likert scale. The research results show that the public has adequate (good) knowledge and perceptions regarding the government's plans to implement the redenomination policy. The amount of income has no implications for the public's perception regarding the redenomination plan that will be implemented by the government, and the level of education has no implications for the public's perception regarding the redenomination plan that will be implemented by the government.